A Critical Analysis of Prosthetic Augmentation of Autologous Microvascular Breast Reconstruction. Issue 6 (June 2020) - Piper, Merisa L.; Lentz, Rachel; Gomez-Sanchez, Clara; Withers, Jacquelyn; Hu, Allison; Sbitany, Hani
Abstract : Introduction: The combined approach using both an implant and autologous tissue for breast reconstruction has become more common over the last 10 years. We sought to provide a systematic review and outcomes analysis of this technique. Methods: We searched PubMed and the Cochrane Library database to identify studies that described implant augmentation of autologous flaps for breast reconstruction. The references of selected articles were also reviewed to identify any additional pertinent articles. Results: We identified 11 articles, which included 230 patients and 378 flaps. Implants used ranged in size from 90 to 510 cc, with an average size of 198 cc. Implants were more frequently placed at the time of autologous reconstruction and in the subpectoral plane. There were no total flap losses, and partial flap loss occurred in 3 patients (1%). There were no cases of venous or arterial thrombosis and no early return to the operating room for flap compromise. Eight implants (2%) were lost because of infection or extrusion, and capsular contracture occurred in 9 breasts (3%). When stratified by the timing of implant placement (immediate vs delayed), there were no significant differences in any postoperative outcomes except the immediate group had a higher infection rate. Conclusions: The criteria for women to be candidates for autologous tissue breast reconstruction can be expanded by adding an implant underneath the flap. We found the overall flap loss rate is comparable with standard autologous flap reconstruction, and the implant loss rate is lower than that in patients who undergo prosthetic reconstruction alone.